From Making "Tools" to Becoming "People" -- The Transformation and Experience of American Educational Punishment Governance: The Transformation and Experience of American Educational (Journal of Education and Development, 2022)
In recent years, it has been known from the network news that American school bullying incidents are frequent, its severity and concealment are gradually increasing, and the main body of bullying is also getting younger and younger. American bullying not only causes severe damage to the physical and mental health of minors but destroys the order of the daily management of the school and also increases the risk of the safety of the campus, on the harmfulness of more significant social issues, such as the United States in most cases, it still takes criticism education some force weaker moral means, the effective governance bullying is not enough. The rule of law is the most effective way to achieve social governance. Every student's campus life is a drill for the future in social life. Their behaviour will eventually affect the public social order. Therefore, American society has put forward a zero-tolerance policy for school bullying. Many public schools in the United States have the characteristics of exclusion, punishment, and decriminalization in managing students' violations and malicious bullying. It not only fails to give full play to the educational nature of punishment effectively but also aggravates severe social problems such as minors dropping out of school, low-school employment, and juvenile delinquency, which increases the educational cost of American society and the cost of colonial governance and management. Under the guidance of the concept of supporting policy, the federal government by eliminating the repellent of early childhood environment discipline, creating a safe and supportive learning environment, promote education in different stages of the field to carry out the resilience measures such as justice, fair and continue to encourage educational discipline, promote the development of children's social emotion and behavior, to guide students to learn and grow in the wrong, American academic punishment has successfully realized the successful transformation of teaching philosophy and education reform, which is worthy of practical reference and complete reference for China's current treatment of school bullying incidents. Better promoting Chinese education can also embark on equitable and healthy future development.